Effect of Wood Hemicellulose Composition on Binding Interactions with Caffeine - Klára Kobetičová (MDPI AG, 2021)
Wood is one of the important construction materials and it is necessary to protect it from biological pests. Hemicellulose in wood consist of various sugar hexoses or pentoses depending on the tree species. This composition can have significant effects on interactions with chemical substance as biocides or coatings. Interactions of glucose, arabinose, mannan, galactomannan, glucogalactomannan, xylan, and hemicellulose corresponding its structure in spruce, pine and beech with biocidal substance caffeine was studied in the present study. Chemical analyses were performed spectrometrically at the caffeine optimal wavelength of 287 nm. The results indicate variable rate of interactions between caffeine and the tested sugar monomers or polymers. The largest interactions between caffeine were observed for simple sugars glucose (71%) and arabinose (67%). Mannan and hemicellulose composted of mannan units had very low interactive potential with caffeine (1–9%), the models of woody plants showed no statistically significant difference (25–30%). Nevertheless, hemicellulose in some previous research showed less potential to bind caffeine than lignin, but greater than completely inactive cellulose. It is evident that the structure of individual sugars and their mixture in polymer hemicellulose has effects on binding interactions with caffeine; however, other research in this area will be necessary in the future.